How Multinational Subsidiary Mandates are Gained and Lost - Birkinshaw, Julian (Journal of International Business Studies, 1996)
A subsidiary mandate is a business, or element of a business, in which the subsidiary participates and for which it has responsibilities beyond its national market. This research studied thirty-one mandates in six Canadian subsidiaries of U.S.-owned multinational corporations. A life-cycle framework was proposed, and used to explore the factors associated with the gain, development and loss of mandates by subsidiaries. Two key findings emerged. First, it was shown that there is a risk in having a full-scope world product mandate, because it is possible to become marginal to the corporate strategy. Second, it was observed that the engine of subsidiary growth is its distinctive capabilities, and that for a mandate to be effective it must be built on those capabilities. Implications for mandate sustainability are proposed on the basis of these two insights.